It's a Sin: AIDS as incipient crisis. (February 2023) - Griffin, Hollis
The HBO miniseries It's a Sin (2021) offers viewers a kind of social history of the AIDS epidemic in the U.K. Across its five episodes, the program depicts ordinary people's first encounters with the pandemic as they manage misinformation, overcome their disbelief, and, eventually, come to terms with the shock and trauma of its impact on the gay male communities of 1980s-era London. The result is a program in which viewers are asked to question how they might have navigated past events under such circumstances, a period in which a mysterious illness moved from the shadowy periphery to the very center of a community's existence.